What determines foreign direct investment to India's pharmaceutical sector? Intellectual property implementation versus inherent institutional strength. (20th July 2022) - Bhandarkar, Supriya; Rajeev, Meenakshi
Abstract: The Indian pharmaceutical industry has assumed importance during the time of the pandemic. Historically, the absence of an intellectual property rights (IPR) regime in India helped reverse‐engineer products, leading to an exponential growth of the industry. This, however, disincentivised foreign direct investment (FDI) needed for innovation. The ratification of the Trade‐Related Aspects of Intellectual Property Rights (TRIPS) agreement in 1995 increased the confidence of foreign investors, allowing FDI inflow into the sector. However, we argue that the mere adoption of TRIPS is not sufficient for FDI and that its enforcement along with other institutional factors such as corruption and political stability play a crucial role. We also take into account competition for FDI among similarly placed nations, in this case from China. Methodologically, we construct a pharmaceutical patent index that measures the legal framework of IP protection specifically for the sector. An ARDL model using data from 1990 to 2019 shows that while the introduction of IPRs helped the inflow of FDI, the enforcement of these rights, as measured by the strengthening of the patent index, has led to a decrease in FDI. Interestingly, our results also show that India's own core competencies such as improving political stability while reducing corruption and trade barriers were the most dominant determinants. Through developing a concise sector‐specific patent index and taking into account institutional determinants, FDI inflow is analysed in a manner not studied otherwise.